Investigation of adsorption/desorption performance by aminopropyltriethoxysilane grafted onto different mesoporous silica for post-combustion CO2 capture. Issue 2 (1st April 2020) - Muchan, Pailin; Saiwan, Chintana; Nithitanakul, Manit
Abstract: Mesoporous silicas with hexagonal structure (MCM-41 and SBA-15) and cubical interconnected pore structure (KIT-6) were synthesized and modified with aminopropyltriethoxysilane (APTES) for using as adsorbents in carbon-dioxide (CO2 )-adsorption application. The CO2 -adsorption experiment was carried out at room temperature and atmospheric pressure using 15% CO2 with a flow rate of 20 mL/min and the desorption experiment was carried out at 100°C under N2 balance with a flow rate of 20 mL/min. The adsorption capacity and adsorption rate of all modified mesoporous silicas were enhanced due to the presence of primary amine in the structure, which was able to form a fast chemical reaction with CO2 . All adsorbents showed good adsorption performance stability after using over five adsorption/desorption cycles. Due to the effect of the adsorbents' porous structure on the adsorption/desorption process, an adsorbent with sufficient pore-size diameter and pore volume together with interconnected pore, KIT-6, represents a promising adsorbent that gave the optimum adsorption/desorption performance among others. It showed reasonable adsorption capacity with a high rate of adsorption. In addition, it could also be regenerated with 99.72% efficiency using 12.07 kJ/mmolCO2 of heat duty for regeneration. Abstract : Capture of CO2 from fossil-fuel combustion sources using solid adsorbents is one of the potential alternatives to liquid solvents like MEA. In this paper, mesoporous silicas with hexagonal structure and cubical interconnected pore structures were synthesized and modified with grafted amines. Graphical Abstract: